2016
DOI: 10.1038/nmeth.3830
|View full text |Cite
|
Sign up to set email alerts
|

Standardized benchmarking in the quest for orthologs

Abstract: Achieving high accuracy in orthology inference is essential for many comparative, evolutionary and functional genomic analyses, yet the true evolutionary history of genes is generally unknown and orthologs are used for very different applications across phyla, requiring different precision-recall trade-offs. As a result, it is difficult to assess the performance of orthology inference methods. here, we present a community effort to establish standards and an automated web-based service to facilitate orthology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
251
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(251 citation statements)
references
References 60 publications
0
251
0
Order By: Relevance
“…Access to data generated by benchmarking tools can easily improve the precision of newly developed tools by comparing a new method to tools indexed in the benchmarking study. Results of the benchmarking study can either be downloaded and the analysis locally run, or researchers can upload their own results and obtain a comparison through an online interface 17,18 . In both cases, benchmarking data allows researchers to easily compare newly developed tools against existing tools without installing and running third-party softwareoften an extremely complicated and time-consuming process, especially when the software lacks detailed documentation 17 .…”
Section: Solution: Systematic Benchmarkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to data generated by benchmarking tools can easily improve the precision of newly developed tools by comparing a new method to tools indexed in the benchmarking study. Results of the benchmarking study can either be downloaded and the analysis locally run, or researchers can upload their own results and obtain a comparison through an online interface 17,18 . In both cases, benchmarking data allows researchers to easily compare newly developed tools against existing tools without installing and running third-party softwareoften an extremely complicated and time-consuming process, especially when the software lacks detailed documentation 17 .…”
Section: Solution: Systematic Benchmarkingmentioning
confidence: 99%
“…al. 18 19 showed that the accuracy of cell population identification from flow cytometry data can be improved by combining predictions from individual computational algorithms.…”
Section: Solution: Systematic Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources differ as to whether given genes are orthologs and if so, what type (e.g., least diverged ortholog, paralog, one-to-one, many-to-many, etc.) (O'Brien et al 2005;Altenhoff et al 2016). In the above example, the zebrafish has two copies of the SKI ortholog: skia and skib.…”
mentioning
confidence: 99%
“…The analysis of synteny in the gene order sense has several applications in genomics. Shared synteny is one of the most reliable criteria for establishing the orthology of genomic regions in different species (Dewey, 2011;Altenhoff et al, 2016). Additionally, exceptional conservation of synteny can reflect important functional relationships between genes.…”
Section: Comparative Genomics and Syntenymentioning
confidence: 99%